التطور التشريعي لقانون الاستثمار في الجزائر - لمياء بلعيسي (المسيلة, 2022)
The legal system of investment in Algeria and France, despite the diversity of its components, complexities and complexity among the various branches of public and private law, is well known. Several developments from the 1960s to the present day in terms of legislative texts This system consists of legal and procedural rules adopted by the host State with a view to attracting foreign capital through the development of incentive measures in administrative, penal, financial and other matters, Its objective and procedural safeguards met international requirements and kept pace with developments and developments. The study was aimed at identifying the legislative evolution of Algeria's investment law both formally and objectively. Keywords: Investment, Legislative Development, Investment Law
Keywords: الاستثمار - التطور التشريعي - قنون الاستثمار